The fighting Fifteenth Alabama Infantry : a Civil War history and roster - Faust, James P., 1953- (McFarland & Company, Inc., Publishers, 2015)
"This volume chronicles the 15th Alabama Infantry Regiment's experiences from its organization in July, 1861, through its surrender at Appomattox. Accounts are given of the 15th's action at Shenandoah, Gettysburg, Chickamauga and Spotsylvania, along with descriptions of camp life. Service records of each member are provided, including enlistment, hometown, battle wounds and, where applicable, cause of death"--